Different contribution of exoelectrogens in methanogenesis via direct interspecies electron transfer (DIET) by the different substrate in continuous anaerobic bioreactor. (November 2022) - Lee, Sang-Hoon; Kang, Hyun-Jin; Kim, Yonghoon; Kim, Na-Kyung; Park, Hee-Deung
Graphical abstract: Highlights: Acetate-fed conditions showed higher methanogenesis performance than that of glucose. Supplemented COD of glucose was cumulated while that of acetate was consumed completely. Different exo- and endoelectrogens were predominated with varying substrate types. Burkholderiaceae driven DIET mechanism was predominant in continuous bioreactors. Abstract: Direct interspecies electron transfer (DIET) is a syntrophic mechanism for electron transfer between exo- and endoelectrogens. Previous studies have demonstrated that methanogenesis performance was significantly improved via the DIET mechanism through conductive materials (CMs) under batch conditions with a single substrate, while that under continuous condition is still under investigation. To investigate how the DIET via CM on methanogenesis performance was changed in response to the different substrates (acetate versus glucose)-fed in continuous anaerobic bioreactors, continuous bioreactors were operated by cross-feeding with acetate and glucose. Acetate-fed conditions showed 0.40 day shorten lagtime, 1.88- and 1.22-folds higher methane production rate, and ultimate methane production than glucose-fed conditions, respectively. Burkholderiaceae- and Anaerolineaceae -related exo-electrogenic populations were enriched with low abundance of Geobacter species in batch reactors. Furthermore, influent substrates affected the distribution of the enriched populations. Taken together, the results suggested that different syntrophic associations contributed methane production by DIET in continuous bioreactors.